Do probiotics decrease the frequency of upper respiratory infections (URIs) in young children?. Issue 9 (September 2015) - Takahashi, Jonathan; Rakel, David
Abstract : Case : During a well‐child visit, the mother of a 5‐year‐old boy and a 3‐year‐old girl laments that her kids "are always getting colds during the winter, " and she wonders if there is a medicine she can give them "to help them catch colds less often." What can you suggest?